Physical Properties of Bael (Aegle marmelos) - Dr. S. P. Divekar; V. P. Khambalkar; R. R. Tembhurne; A. A. Magar; C. D. Nikole (International Journal of Engineering and Management Research, 2020)
Aim: To determine the physical properties of Bael such as moisture content, spatial dimensions, geometric mean diameter, sphericity, roundness, bulk density, true density, angle of repose, coefficient of friction. Methodology: The total 40 numbers of samples were taken for determination of spatial dimensions for Bael, small and large were divided in two Grades of A and B respectively. Physical properties of bael are required for the designing of the decortications machine. Results: The special dimensions, that is length, breadth, thickness, geometric mean diameter and sphericity for grade A of beal was to be 56.068 mm, 60.53 mm, 659.6 mm, 58.68 mm and 0.96 respectively. The special dimensions, that is length, breadth, thickness, geometric mean diameter and sphericity for grade B of beal was to be 62.83 mm, 72.18 mm, 70.14 mm, 65.80 mm and 0.94 respectively. The average bulk density, true density and porosity of Grade A were 0.337 g/cc, 1.191 g/cc and 71.0% respectively. The average bulk density, true density and porosity of Grade B were 0.0.274 g/cc, 1.094g/cc and 74.28 % respectively. The average angle of repose and coefficient of friction of bael were 33.88º and 0675. Interpretation: The cutting efficiency of wood apple cutting machine for bael was 90.43% and damage percentage of wood apple cutting machine for bael was 9.56%.